Experimental evidence of pharmacological management of anchorage in Orthodontics: A systematic review - Felipe José Fernández-González; Aránzazu Cañigral; Felipe Balbontín-Ayala; José Manuel Gonzalo-Orden; Felix de Carlos; Teresa Cobo; Jose Pedro Fernández-Vázquez; Fernando Sánchez-Lasheras; José Antonio Vega (Dental Press Editora, 2015)
Introduction: Orthodontic anchorage is one of the most challenging aspects of Orthodontics. Preventing undesired movement of teeth could result in safer and less complicated orthodontic treatment. Recently, several reviews have been published about the effects of different molecules on bone physiology and the clinical side effects in Orthodontics. However, the effects of local application of these substances on the rate of orthodontic tooth movement have not been assessed.Objectives: The aim of this research was to analyze the scientific evidence published in the literature about the effects of different molecules on orthodontic anchorage.Methods: The literature was systematically reviewed using PubMed/Medline, Scopus and Cochrane databases from 2000 up to July 31st, 2014. Articles were independently selected by two different researchers based on previously established inclusion and exclusion criteria, with a concordance Kappa index of 0.86. The methodological quality of the reviewed papers was performed.Results: Search strategy identified 270 articles. Twenty-five of them were selected after application of inclusion/exclusion criteria, and only 11 qualified for final analysis. Molecules involved in orthodontic anchorage were divided into three main groups: osteoprotegerin (OPG), bisphosphonates (BPs) and other molecules (OMs).Conclusions: Different drugs are able to alter the bone remodeling cycle, influencing osteoclast function and, therefore, tooth movement. Thus, they could be used in order to provide maximal anchorage while preventing undesired movements. OPG was found the most effective molecule in blocking the action of osteoclasts, thereby reducing undesired movements.